A process philosophy framework for film theory and aesthetics. Issue 2 (3rd April 2019) - Branigan, Edward
ABSTRACT: Process Philosophy has a long history as a disciplined way of thinking about the world. Process thinking flows in film theories, too, though often unacknowledged as a framework. This essay contrasts process and substantialist accounts of the world, film, and aesthetics. Processual accounts promise new descriptions of photography, film, color, narrative, narration, fiction, the camera, semiotics, and the self. Performative aspects of aesthetic texts may be measured by such dynamic events as temporal gestalts, patterning, procedural schemata, judgment heuristics, working memory (which includes the stream of consciousness, adverbial sensing, and a flowing sense of selfhood), projections, radial associations, reidentifications (frequency, vibration), and the ever-present possibilia of paradigms and the nearly true. Processes engender immediacy and directionality – a flow toward continual becoming. The result is a new perspective on the nature of textuality – its fluid properties, its collective behavior – without necessarily displacing substantialist accounts that rely on long-term memory and the immobile signposts of sign, cue, form, and thingness.